The Success Rate of Two Explant Types of Stevia (Stevia rebaudiana Bertoni) in Various Sterilant Formulas - Kariena, Riedha; Hardarani, Nofia; Susanti, Hilda (Journal of Tropical Horticulture, 2020)
This study aims to determine the effect of interaction between several sterilants and types of explants and determine the best interaction with stevia culture's success rate. This study was designed using a Factorial Complete Randomized Design with two factors and three replications. The first factor is sterilant formulas i.e: fungicide 3% + alcohol 70% + Bayclin 5%; fungicide 3% + bactericide 6% + 70% alcohol + Bayclin 5%; sublimate 0.1% + 70% alcohol + Bayclin 5%; and fungicide 3% + bactericide 6% + sublimate 0.1% + alcohol 70% + Bayclin 5%. The second factor is explant types, i.e., stevia nodes and leaves. The variables observed are the percentage of contamination (%), percentage of alive explants (%), and browning percentage.Â  The interaction between sterilants and explant types only had a significant effect on the percentage of alive explants. The best interactions of sterilant formulas and explant types on the percentage of alive explants are 0.1% sublimate + 70% alcohol + 5% Bayclin and leaf explants.